2022
DOI: 10.1038/s41467-022-33129-8
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional interfacial water structure of highly concentrated aqueous electrolytes at negative electrode polarizations

Abstract: Water-in-salt electrolytes are an appealing option for future electrochemical energy storage devices due to their safety and low toxicity. However, the physicochemical interactions occurring at the interface between the electrode and the water-in-salt electrolyte are not yet fully understood. Here, via in situ Raman spectroscopy and molecular dynamics simulations, we investigate the electrical double-layer structure occurring at the interface between a water-in-salt electrolyte and an Au(111) electrode. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 60 publications
0
51
0
Order By: Relevance
“…The basic HB structure of the bulk phase of Na 2 SO 3 solution with different mass fractions has been introduced in the first part of this work. In the aqueous solution system above metal electrode, the essence of the geometric structure of the EDL at the solid–liquid interface where the electrochemical reaction takes place is the HB network composed of water molecules and ions . Therefore, a thorough understanding of EDL structures is crucial for clarifying the electrode reaction mechanism and performance. , The analysis of the internal structure of the EDL is based on a full understanding of the corresponding HB structure, which is still a challenging topic. To analyze the stability of the SO 3 2‑ ion at different adsorption sites, the geometry of the initial and stability configurations is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic HB structure of the bulk phase of Na 2 SO 3 solution with different mass fractions has been introduced in the first part of this work. In the aqueous solution system above metal electrode, the essence of the geometric structure of the EDL at the solid–liquid interface where the electrochemical reaction takes place is the HB network composed of water molecules and ions . Therefore, a thorough understanding of EDL structures is crucial for clarifying the electrode reaction mechanism and performance. , The analysis of the internal structure of the EDL is based on a full understanding of the corresponding HB structure, which is still a challenging topic. To analyze the stability of the SO 3 2‑ ion at different adsorption sites, the geometry of the initial and stability configurations is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In the aqueous solution system above metal electrode, the essence of the geometric structure of the EDL at the solid−liquid interface where the electrochemical reaction takes place is the HB network composed of water molecules and ions. 39 Therefore, a thorough understanding of EDL structures is crucial for clarifying the electrode reaction mechanism and performance. 40,41 The analysis of the internal structure of the EDL is based on a full understanding of the corresponding HB structure, which is still a challenging topic.…”
Section: Adsorption Of Somentioning
confidence: 99%
“…Classical MD (CMD) has been widely used to investigate the concentrated electrolytes, and can offer microscopic information on solvation structures of concentrated electrolytes and electrode/electrolyte interfaces. ,, Careful parametrization is essential to ensure the accuracy of the CMD simulations, and even so, CMD may not give reliable results in difficult cases such as highly concentrated electrolytes . To avoid the uncertainty in force field parameters and more importantly compute the redox potential of TFSI – , AIMD is used to calculate concentrated electrolytes in this work. , …”
Section: Methods Sectionmentioning
confidence: 99%
“…Recently, lots of efforts have been devoted to understanding the interfacial structures of WiSE on anode surface and how they affect the SEI formation. For example, Lian et al found that the interfacial water can not serve as H-bond acceptors but donors due to the coordination of Li + , which provides atomistic insight into desolvation process and layered accumulation of Li + on anode surface . On the other hand, it should be noted that the bulk thermodynamics (e.g., reduction potential of TFSI – in bulk solution) determines whether the SEI would form at the first place in the initial charging cycle.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] Furthermore, recent studies have shown that highly concentrated electrolytes exhibit an unusual interfacial H2O structure. 44,46 Therefore, highly concentrated electrolytes can be used to uncover the role of H2O in controlling kinetic branching between the C1 and C2+ pathways without the use of an organic co-solvent.…”
mentioning
confidence: 99%